Outcomes of thoracic endovascular aortic repair with chimney technique for aortic arch diseases - Li, Jiehua; Xue, Yunfei; Li, Shangqian; Sun, Likun; Wang, Lunchang; Wang, Tun; Fang, Kun; Luo, Mingyao; Li, Xin; He, Hao; Li, Ming; Li, Quanming; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective This study aimed to summarize the long-term experience of using the chimney technique in thoracic endovascular aortic repair (TEVAR) for aortic arch diseases. Methods From November 2007 to June 2021, a total of 345 consecutive patients (mean age 56 ± 11.3 years, range 28–83, 302 men) with aortic arch pathologies underwent TEVAR combined with chimney technique (cTEVAR). Their medical data and follow-up results were retrospectively reviewed and analyzed. Results Among the 345 patients, 278 (80.6%) received single chimneys, 53 (15.4%) received double chimneys, 7 (2%) received triple chimneys, and 7 (2%) underwent cTEVAR accompanied by other techniques (two with extra-anatomical bypass, two with in situ fenestration, and three with physician modified fenestration). A total of 412 chimney stents were used, including 27 in the innominate artery (IA), 113 in the left common carotid artery, 270 in the left subclavian artery, and two in the aberrant right subclavian artery. Early type IA endoleaks were found in 38 (11%) patients, including 12 with the double or triple chimney technique. Early type II endoleak was found in nine (2.6%) patients. Early re-intervention occurred in two patients with double chimney technique, one for chimney stent migration and the other for compression of chimney stent. The 30-day mortality was 1.2% (4 in 345). During a mean follow-up of 42 ± 22 months (range 1–108 months), major stroke occurred in nine (2.6%) patients, chimney occlusion or stenosis occurred in six (1.7%), and retrograde type A aortic dissection occurred in four (1.2%). Fourteen (4.1%) patients received the secondary intervention. The all-cause mortality was 6.7% (23 in 345). Additionally, the total adverse event rate after cTEVAR was 13.9% (48 in 345). Conclusion TEVAR with chimney technique provides a minimally invasive alternative with good chimney graft patency and low postoperative mortality during follow-up. However, the double and triple chimney techniques should be used cautiously as they seem to have a higher risk for type IA endoleak and adverse events after the operation.